Climate Changes and the Imperatives of All Round-a-Year Human Activity in the Arctic - L. Voronkov (Международная аналитика, 2015)
The author questions the indisputability of the Arctic’s existing climate change assessments and insists on the need to adjust the Arctic strategies of states to different scenarios of such changes. While not denying the impact of human society on the Earth’s climate, the author believes to be important not to limit research on its changes by exclusively natural-scientific aspects, but to include considerations concerning the influence of peculiarities of human society’s development on the climate. He thinks it is important to take into account the combine impact of the changing nature of contemporary industrial activity, of sources for energy supply, the on-going processes of building of “smart” economy and its innovative development, demographic changes, improvement of human capital as well as the impact of increased environmental consciousness of human beings on the global and Arctic climate. Despite the observed climatic changes in the Arctic, it remains ice-covered the major part of the year. Any commercially justified human activities in the Arctic must be based on the need to maintain a year-round exploitation of its resources and possibilities and to create the appropriate infrastructure, machinery and equipment. The author comes to the conclusion that the need to resolve these problems requires considerable financial resources and time.